El abandono de la causa en materia laboral, de acuerdo al código orgánico general de procesos - Puetate Castro, Janeth Lucía (2017)
In addition to the fact that the Labor Code establishes that workers' rights are inalienable and imprescriptible - retirement - Article 33 of the Constitution recognizes work as a right and a social duty, and an economic right, a source of personal fulfillment and Base of the economy. Breaking down the statement we have the work:  It is a personal right;  It is an economic right;  It is a source of personal fulfillment; Y,  It is the basis of the state economy. Rights and characteristics that oblige the State to proportionate and guarantee adequate protection. Now, article 247 of the General Organic Code of Processes makes the exceptions of the causes in which abandonment does not proceed and says: "Not permissible abandonment. The abandonment is not possible in the following cases: 1. In cases involving the rights of children, adolescents or the incapacitated. 2. When the actors are the institutions of the State. 3. At the stage of execution ". As we can see within these exceptions are not the causes in which the rights of workers are involved and that these are the triggers, resulting in negative discrimination, ignorance of constitutional protection, and regressive attitude of the General Organic Code of Processes . Without undermining the rights of children or the rights of the State, one must be consistent in legislating and recognizing that precisely the rights of children, in large part, and those of the State, and to a great extent, are covered by the activity and Labor force, so that, at least, this labor force, should be equated with the rights of children and the State, recognizing that their rights are not susceptible of abandonment. To keep the norm as it is is to continue to maintain corporate or employer hegemony over the rights of workers, a weaker part of the employment relationship, and deny them due process and leave them defenseless. That is why this subject has been investigated and through a theoretical, doctrinal, critical and normative analysis on the work activity, has reached very important conclusions that merit a reform to the General Organic Code of Processes.